Triple jump techniques - Peditto, M.
In many High School track programs, the triple jump is too complex and thus too time consuming for one coach to address properly. Therefore, many jumpers do not have the proper technique they need to succeed. The triple jump itself is a dynamic and challenging event. It requires the precise blend of speed, balance, resiliency, power, and explosion. In order to achieve success in the event, one must not only meet these qualifications, but master them as well. Also, they must maintain them throughout all phases of the jump: the approach, the hop, the skip, and the jump. The following article will teach proper technique for all phases of the triple jump, as well as provide some useful training and conditioning drills.